Systemic and Extraradicular Bacterial Translocation in Apical Periodontitis - Bordagaray, María José; Fernández, Alejandra; Garrido, Mauricio; Astorga, Jessica; Hoare, Anilei; Hernández, Marcela (Frontiers in Cellular and Infection Microbiology, 2021)
Apical periodontitis is an inflammatory disease of microbial etiology. It has been suggested that endodontic bacterial DNA might translocate to distant organs via blood vessels, but no studies have been conducted. We aimed first to explore overall extraradicular infection, as well as specifically by Porphyromonas spp; and their potential to translocate from infected root canals to blood through peripheral blood mononuclear cells. In this cross-sectional study, healthy individuals with and without a diagnosis of apical periodontitis with an associated apical lesion of endodontic origin (both, symptomatic and asymptomatic) were included. Apical lesions (N=64) were collected from volunteers with an indication of tooth extraction. Intracanal samples (N=39) and respective peripheral blood mononuclear cells from apical periodontitis (n=14) individuals with an indication of endodontic treatment, as well as from healthy individuals (n=14) were collected. The detection frequencies and loads (DNA copies/mg or DNA copies/μL) of total bacteria, Porphyromonas endodontalis and Porphyromonas gingivalis were measured by qPCR. In apical lesions, the detection frequencies (%) and median bacterial loads (DNA copies/mg) respectively were 70.8% and 4521.6 for total bacteria; 21.5% and 1789.7 for Porphyromonas endodontalis; and 18.4% and 1493.9 for Porphyromonas gingivalis. In intracanal exudates, the detection frequencies and median bacterial loads respectively were 100% and 21089.2 (DNA copies/μL) for total bacteria, 41% and 8263.9 for Porphyromonas endodontalis; and 20.5%, median 12538.9 for Porphyromonas gingivalis. Finally, bacteria were detected in all samples of peripheral blood mononuclear cells including apical periodontitis and healthy groups, though total bacterial loads (median DNA copies/μL) were significantly higher in apical periodontitis (953.6) compared to controls (300.7), p<0.05. Porphyromonas endodontalis was equally detected in both groups (50%), but its bacterial load tended to be higher in apical periodontitis (262.3) than controls (158.8), p>0.05; Porphyromonas gingivalis was not detected. Bacteria and specifically Porphyromonas spp. were frequently detected in endodontic canals and apical lesions. Also, total bacteria and Porphyromonas endodontalis DNA were detected in peripheral blood mononuclear cells, supporting their plausible role in bacterial systemic translocation.